Uvaia fruit (Eugenia pyriformis Cambess) drying: ethanol as pre-treatment, convective drying kinetics and bioactive compounds - Gomes, Bruna de Oliveira (2022)
Uvaia is a native fruit from the Brazilian Atlantic Forest, whose commercialization is still limited due to its high perishability and seasonality. This study evaluated the effects of ethanol pre-treatment on convective drying and its impacts on the bioactive compounds of uvaia. Six treatments were performed, consisting of control and pre-treated samples by immersion in ethanol (99.8% v/v) for 10 and 20 min, which were subsequently conduced to convective drying (1 m/s) at 40 and 60°C. Sample temperatures were recorded throughout the drying process and the dry products were evaluated for phenolic compounds content and antioxidant capacity. The Page model was used to evaluate the data and study the kinetics. Increasing the temperature reduced drying time by about 50%, while ethanol pre- treatments reduced processing time by 7-31%. The pre-treatment in combination with temperature influenced the drying time and were associated with the penetration of ethanol into the sample and the volatility of the liquid portion. The higher vapor pressure of ethanol, in relation to water, reduced the initial temperature of the treated samples. Drying and pre-treatment temperatures reduced the levels of bioactive compounds, which was associated with degradation and possible extraction by ethanol. Therefore, the advantages of using ethanol as a drying accelerator were discussed, as well as some limitations, mainly in the content of bioactive compounds. Even so, stable dried fruits were obtained, containing adequate levels of bioactive compounds for different applications (direct consumption or for use in formulations).